Analisis Produktivitas Dengan Metode Objective Matrix (OMAX) dan Fault Tree Analysis (FTA) Pada PT. XYZ - Fawzy, Nico Muhammad; Andung Jati Nugroho (Jurnal Penelitian Rumpun Ilmu Teknik, 2023)
PT. XYZ is a foundry company that has difficulty achieving production targets compared to previous years. This study aims to evaluate the level of productivity using the Objective Matrix (OMAX) method. The highest productivity value in September 2022 with a value of 540. Meanwhile, the lowest productivity value was in October 2022 with a value of 340. The amount of total production compared to the total use of raw materials plays an important role in increasing productivity. In the productivity criteria of effective working hours, the criteria of machine working hours, and production effectiveness show good values. While the criteria for the effectiveness of product defects are not good because they show the lowest value. Based on the analysis of the fault tree analysis (FTA) method, it was found that there were 10 basic events that caused problems from low productivity, namely the presence of inexperienced operators, no assembly marks on the mold, no mold density standards, no schedule for calibration, leaky storage roofs, lack of quality control in the supply of raw materials, no separation between raw materials, Sifting is not clean, lack of regular machine maintenance, and induction furnaces that are not cleaned every production session.